Evaluation of the effect of melatonin in patients with Burning mouth syndrome: a double-blind, placebo-controlled randomized clinical trial - Tahereh Nosratzehi; Abolfazl Payandeh; Kosar Arbab (Universidade de São Paulo, 2023)
Abstract The present study was carried out to evaluate the effect of Melatonin and Placebo in the patient with the Burning mouth (BMs). This double-blind, placebo-controlled randomized clinical trial study was carried out on 30 patients who were suffering from BMS. During this period patients were divided into 2 study and control groups. The study group used four 3 mg Melatonin daily and the control group received a placebo. Then the severity of the burning sensation was measured by the physician Sleep quality was measured using the VAS scale using the Petersburg questionnaire. Data in the application Enter SPSS 20 and then using T test or equivalent Nonparametric was analyzed, mean sleep score and mean severity of oral irritation before and after treatment in two the group was evaluated using T-test Independent. Level significance was considered 0.05. The results of the present study show that the use of melatonin and a placebo in patients with BMS reduces sensation and improves their sleep quality, although it may not reduce it completely. In this study severity of burning was 4.93±2.56 after treatment in the study group and 6.93±2.12 in the control group, which was statistically significant (P =0.036). No significant difference was observed between the two groups in the sleep quality score (P-value = 0.43). Using Melatonin can be a reliable way to treat pain for which there is no standard treatment to date. Although evidence suggests an association between sleep disorders and BMS, melatonin was not superior to a placebo in reducing BMS-induced burning in the present study. Identification of stressors and the ways to struggle with them, further studies with larger samples and higher oral doses, extended follow-up periods and control of psychological factors, and measurement of body mass index that may affect pharmacokinetics are recommended.